Assessment of the efficiency of treatment of patients with COVID-19 (literature review) - Moskaliuk, V.D.; Balaniuk, I.V.; Andrushchak , M.O.; Sirota , B.V.; Honcharuk , L.M.; Chernetska, N.V.; Ilika , V.V. (Medicni Perspektivi, 2024)
WHO has recognized that COVID-19 is a global pandemic. In the conditions when COVID-19 continues to spread rapidly throughout the world, covering different groups of the population, and despite the fact that the existing standards of care for these patients are constantly updated, it is urgent to continue the search for new, more effective methods of treatment. Currently, the treatment of patients with COVID-19 remains difficult, since the drugs that have a harmful effect on the virus are at the stage of development and testing. Remdesivir, favipiravir, hydroxychloroquine with or without azithromycin, ivermectin, lopinavir/ritonavir were recommended among the agents for etiotropic therapy. But at present, the WHO notes that there is no evidence to recommend any specific antiviral treatment against COVID-19. The results obtained by conducting multicenter randomized clinical trials, which were conducted in 30 countries of the world and included 11,266 people of different ages, mostly adults and elderly. Unfortunately, the use of plasma from the blood of people who have contracted COVID-19 does not save the lives of seriously ill patients from the need to be connected to a ventilator and does not increase their chances of survival. This is also reported by WHO. In treatment, emphasis is placed on the application of pathogenetic therapy. The main measures of non-specific individual and collective prevention with the introduction of quarantine are briefly given. The article is intended mainly for doctors who work with patients with COVID-19 and contact persons. Treatment of patients with COVID-19, as a rule, is pathogenetic, since there are no specific antiviral drugs.. The decision regarding medical care in an outpatient clinic setting is made after a clinical assessment of the patient's condition and an assessment of home security. People who are at risk of developing complications should be referred for inpatient treatment.